Negativity towards negative results: a discussion of the disconnect between scientific worth and scientific culture - Natalie Matosin; Elisabeth Frank; Martin Engel; Jeremy S. Lum; Kelly A. Newell (The Company of Biologists, 2014)
Science is often romanticised as a flawless system of knowledge building, where scientists work together to systematically find answers. In reality, this is not always the case. Dissemination of results are straightforward when the findings are positive, but what happens when you obtain results that support the null hypothesis, or do not fit with the current scientific thinking? In this Editorial, we discuss the issues surrounding publication bias and the difficulty in communicating negative results. Negative findings are a valuable component of the scientific literature because they force us to critically evaluate and validate our current thinking, and fundamentally move us towards unabridged science.